Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling